Giant Synovial Cyst of Thigh: A Rare Entity - Kushagra Sinha; Rajesh Maheshwari; Atul Agrawal (Case Reports in Orthopedics)
Synovial cyst occurs secondary to traumatic, degenerative, or inflammatory conditions. Synovial cysts represent abnormal distension of bursae, which communicate with the joint. Giant synovial cysts are typically due to rheumatoid arthritis, other causes being trauma and synovial pseudoarthrosis. A 33-year-old male presented to an outpatient clinic with a massive swelling on his posterolateral aspect of right thigh extending from upper one-third to the knee joint which had been increasing in size over the past six months. This was associated with dull aching pain. All laboratory investigations were within normal parameters. Even FNAC was inconclusive. With time, swelling was increasing in size. Ultrasound revealed the cystic nature of swelling. MRI showed large cystic lesion 24 × 10 × 12 cm in posterolateral aspect of thigh extending up to knee joint. Following the MRI, an excision was planned. After excision, histological examination confirmed the synovial nature of the cyst, which had a collagenous wall and dense chronic inflammatory cells. As the disease is extremely rare and asymptomatic, precise diagnosis is difficult and often delayed. We consider that open surgical excision should be reserved for cases of large synovial cysts because it can provide a complete resection of the lesion and minimize the risk of recurrence.